2000
DOI: 10.2135/cropsci2000.403665x
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Soybean Cultivars to Sclerotinia Stem Rot in Field, Greenhouse, and Laboratory Evaluations

Abstract: Simple sequence repeat markers developed from maize se-cytological mapping in rye (Secale cereale L.). p. 121-122 In P.E. McGuire and C.O. Qualset (ed.) Progress in genome mapping of quences found in the GENBANK database: Map construction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(84 citation statements)
references
References 14 publications
1
82
0
1
Order By: Relevance
“…Even with irrigation and inoculation, soybean genotypes vary in canopy architecture, flowering date, and lodging, all of which affect disease development (Boland & Hall, 1987;Miklas et al, 2003;Bolton et al, 2006). Greenhouse and laboratory evaluations are often performed and are an integral part of resistance screening methodology for S. sclerotiorum (Kim et al, 2000;Vuong et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Even with irrigation and inoculation, soybean genotypes vary in canopy architecture, flowering date, and lodging, all of which affect disease development (Boland & Hall, 1987;Miklas et al, 2003;Bolton et al, 2006). Greenhouse and laboratory evaluations are often performed and are an integral part of resistance screening methodology for S. sclerotiorum (Kim et al, 2000;Vuong et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Disease control is mainly based on cultural practices such as reduced or no till systems and crop rotations with corn and cereals (Anderson 1996). Several studies have reported partial resistance among soybean lines and cultivars grown in the northeastern United States and Canada (Cline and Jacobsen 1983;Boland and Hall 1986;Zhang 1995;Kim et al 2000). However complete resistance was not reported.…”
Section: Mots Clésmentioning
confidence: 99%
“…A variety of inoculation methods have been reported to accurately evaluate SSR response in soybean. Inoculation methods were performed on whole plant with mycelium (Kim et al 2000) or ascospores (Cline and Jacobsen 1983), or on excised plant parts with mycelium or oxalic acid, a major determinant of S. sclerotiorum's virulence used to indirectly evaluate the effects of the fungus on soybean explants (Wegulo et al 1998). None of these methods are completely satisfying because they are destructive (e.g., explant methods) or produce inconsistent results due to the variability of inoculum, inoculation method or environmental factors.…”
Section: Mots Clésmentioning
confidence: 99%
See 2 more Smart Citations